Endocrine system disturbances in children with inherited metabolic diseases: a narrative review - Tagi, Veronica Maria; Fiori, Laura; Montanari, Chiara; Tonduti, Davide; Ferrario, Matilde; Gambino, Mirko; Greco, Ilenia Pia; Cecchini, Alessandra; Calcaterra, Valeria; Zuccotti, Gianvincenzo; Verduci, Elvira (Frontiers in Endocrinology, 2025)
Inborn metabolic diseases (IMDs) represent a diverse and complex group of rare disorders, typically resulting from variants in genes that encode specific enzymes or cofactors, leading to reduced or absent enzymatic activity. These conditions commonly disrupt one or more metabolic pathways, often impacting multiple organ systems from early childhood. Clinicians should consider the possibility of an IMD when an endocrine abnormality is accompanied by other unexplained clinical signs or in presence of combined endocrinopathies. While some IMDs associated with endocrine dysfunction in children and adolescents are well-documented and supported by established treatment guidelines, others lack clear recommendations or are characterized by inconsistent data. This narrative review aims to summarize the main IMDs that present with endocrine abnormalities in pediatric patients, organized according to affected organ systems and underlying pathophysiological mechanisms. Furthermore, we reviewed the latest recommendations, when available, for monitoring endocrine function in children with these disorders and eventually for providing a tailored treatment, where applicable.